2017
DOI: 10.1002/chem.201704167
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biology of Teixobactin

Abstract: Bacterial resistance to existing drugs is becoming a serious public health issue, urging extensive search for new antibiotics. Teixobactin, a cyclic depsipeptide discovered in a screen of uncultured bacteria, shows potent activity against all the tested Gram-positive bacteria. Remarkably, no teixobactin-resistant bacterial strain has been obtained despite extensive efforts, highlighting the great potential of teixobactin as a lead compound in the fight against antimicrobial resistance (AMR). This review summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 73 publications
0
50
0
Order By: Relevance
“…In less than three years since its discovery, more than a hundred analogues have been synthesised by various research groups in the hope of elucidating its structure–activity relationships (SARs) . The biological activities of these analogues and the different synthetic strategies reported have been comprehensively reviewed . X‐ray crystallographic, molecular dynamic and NMR structural studies have also been conducted to construct possible binding models of the native peptide and its analogues .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In less than three years since its discovery, more than a hundred analogues have been synthesised by various research groups in the hope of elucidating its structure–activity relationships (SARs) . The biological activities of these analogues and the different synthetic strategies reported have been comprehensively reviewed . X‐ray crystallographic, molecular dynamic and NMR structural studies have also been conducted to construct possible binding models of the native peptide and its analogues .…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The biological activities of these analogues and the different synthetic strategies reported have been comprehensively reviewed. [38,39] X-ray crystallographic, molecular dynamic and NMR structural studies have also been conducted to construct possible binding models of the native peptide and its analogues. [26,27,40] Additionally,i narecent mini-review, we provideda ni nsighti nto the structural similarities of teixobactin with other lipid II inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Several hundred teixobactin analogues have already been evaluated, with most modifications only involving amino acid substitutions . N ‐methylation is observed in non‐ribosomal depsi‐ peptides and can greatly impact their pharmacological activity .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that the activity of teixobactin is highly sensitive to modification, but substitutions are moderately tolerated at residues 3, 4, 9, and 10 . Replacement of l ‐ allo‐ End 10 with natural commercially available amino acids such as l ‐leucine is desirable for rapid SAR studies since the former is both synthetically challenging and difficult to incorporate into the peptide.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the synthesis of cyclic depsipeptides, either in solution or on solid 6 phase, has only been reported for those peptides bearing an ester bond involving the ß-hydroxyl group of a Ser or a Thr residue. [30][31][32][33][34] Recently, we have established a convenient solid-phase strategy for the preparation of the macrolactone of eight amino acids present in fengycins. 35 The key steps of the synthesis were the formation of the phenyl ester bond and the on-resin head-to-side-chain cyclization.…”
Section: Introductionmentioning
confidence: 99%